THE HYBRID COUMPOUNDS AND THE INFLUENCE OF HYDROGEN BONDING (Journal of Sciences & Technology, 2016)
Organic–inorganic hybrid materials have received increasing attention in recent research particularly because of their ability to combine the specific properties of inorganic frameworks and the features of organic molecules, including the formation of weak interactions. These materials have recently attracted further interest due to their attractive potential for application as insulators in the electronics industry. They offer promising opportunities for the development of efficient conductors, ferroelectrics, and semiconductors in a wide range of electronic applications [1,2]. The hybrid compounds are rich in H-bonds and they could be used to this effect because of their potential importance in constructing sophisticated assemblies from discrete ionic or molecular building blocks due to its strength and directionality. In order to enrich the varieties in such kinds of hybrid materials and to investigate the influence of hydrogen bonds on the on the structural features, they have synthesized a new compound, This kind of hydrogen bonding appears in the active sites of several biological systems and is observed in similar previously studied hybrid compounds.